From Cyclopentasilane to Thin‐Film Transistors. (23rd December 2020) - Gerwig, Maik; Ali, Abid Shaukat; Neubert, David; Polster, Sebastian; Böhme, Uwe; Franze, Georg; Rosenkranz, Marco; Popov, Alexey; Ponomarev, Ilia; Jank, Michael P. M.; Viehweger, Christine; Brendler, Erica; et al.
Abstract: Cyclopentasilane (CPS) has been studied as an liquid precursor for the deposition of thin silicon films for printed electronics and related applications. The processing involves a UV‐induced prepolymerization of CPS followed by liquid deposition and low‐temperature thermolysis. An insight into the oligomer and polymer formation including crosslinking in solution using 29 Si NMR spectroscopy and electron spin resonance spectroscopy is reported. Formation of SiH (T‐units) and SiH3 (M‐units) is observed as well as short‐lived paramagnetic species. Additionally, the polymerization is followed by Raman spectroscopy. Reactive molecular dynamics simulations are applied to develop a theoretical model for the CPS‐ring‐opening and crosslinking steps. The experimental and computational data correspond well to each other and allow insight into the mechanism of polymer formation. The processing steps include spin‐coating, thermal drying, and conversion to amorphous silicon, H‐passivation, and fabrication of a CPS‐derived thin‐film transistor (TFT), without intermediate silicon crystallization. Further improvement is gained by using tetralene as a solvent, leading to a reduction of the time‐consuming polymerization step by one order of magnitude compared to cyclooctane. The overall quality and characteristics of the CPS‐derived spin‐coated silicon thin films correspond to standard plasma enhanced chemical vapor deposition‐derived devices with respect to performance levels. Abstract : Cyclopentasilane is UV‐prepolymerized followed by spin‐coating, drying, H‐passivation, and fabrication of thin film transistors (TFTs), without Si‐crystallization. Oligomer/polymer formation was studied using 29 Si NMR, Raman, and electron spin resonance spectroscopy, indicating T‐/M‐units and short‐lived paramagnetic species. Atomistic simulations are applied to develop theoretical models which correspond well with experimental data. Analysis of the TFT quality indicates suitability for electronics applications.